Semantic query Cache using Dynamic Facts (SCDF): a novel approach to efficient information retrieval. (14th July 2008) - Sumalatha, M.R.; Vaidehi, V.; Kannan, A.
XML query engines can be exploited by caching technology to reduce the latency caused by data transmission. This paper reports on a caching system designed to facilitate XML query processing in the Web. It provides an alternative approach to other architectures, in which the unit of transfer is a page or a tuple. Semantic caching gives enhanced performance based on the result sets of previously answered queries when compared with other systems. A mechanism capable of caching previously computed results for answering future queries with a knowledge-based analysis would be beneficial for improving performance. We have proposed a framework Semantic Cache using Dynamic Facts, which improves the query response reducing network traffic.